Finding the average rate of change of a function Find the average rate of change of \( g(x)=3 x^{2}-2 x \) from \( x=-4 \) to \( x=-2 \). Simplify your answer as much as possible. \( \square \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To find the average rate of change of the function \( g(x)=3 x^{2}-2 x \) from \( x=-4 \) to \( x=-2 \), you first need to evaluate the function at both points. Calculate \( g(-4) \): \[ g(-4) = 3(-4)^2 - 2(-4) = 3(16) + 8 = 48 + 8 = 56 \] Now calculate \( g(-2) \): \[ g(-2) = 3(-2)^2 - 2(-2) = 3(4) + 4 = 12 + 4 = 16 \] Now, use the formula for the average rate of change: \[ \text{Average Rate of Change} = \frac{g(-2) - g(-4)}{-2 - (-4)} = \frac{16 - 56}{-2 + 4} = \frac{-40}{2} = -20 \] So, the average rate of change of \( g(x) \) from \( x=-4 \) to \( x=-2 \) is \( -20 \).